Comparison of combined intravenous and inhalation anesthesia and total intravenous anesthesia in laparoscopic surgery and the identification of predictive factors influencing the delayed recovery of neurocognitive function - Song, Teng; Wu, Li-Jun; Li, Li (Frontiers in Medicine, 2024)
Background Compare the anesthesia effects of combined intravenous and inhalation anesthesia (CIVIA) and total intravenous anesthesia (TIVA) in laparoscopic surgery. Furthermore, our objective is to examine the elements that contribute to the delay in postoperative recovery of neurocognitive function and anticipate the manifestation of delayed recovery by analyzing serum cytokines. Methods The CIVIA group and the TIVA group both consisted of 130 patients who were scheduled to have elective major abdominal surgery through laparoscopy. The criteria taken into account by the observational and record-keeping study were the patients’ ages, sexes, body masses, heights, and the presence or absence of any preexisting problems. Both groups also had their anesthetic depth, duration, and per-unit-of-time muscle relaxant and analgesic dosages recorded. Finally, the length of each patient’s stay in the hospital as well as their overall length of stay were tracked. By using the Mini-Mental State Examination (MMSE) to measure cognitive function, we assessed the mental states of the subjects. Additionally, we wanted to identify any biomarkers that could be linked to postoperative cognitive decline or delays in neurocognitive recovery. Results A total of 51 participants from the CIVIA group and 53 participants from the TIVA group satisfactorily completed the necessary neuropsychological exam for identifying delayed neurocognitive recovery at the study’s completion. In the initial data of the two groups, no significant discrepancies were found (p > 0.05). The CIVIA group exhibited noteworthy reductions in the quantity of administered analgesics and muscle relaxants per unit of time in comparison to the TIVA group (p < 0.05). In addition to this, the duration from the sevoflurane tank being closed to the extubation period demonstrated a significant reduction in the CIVIA group compared to the TIVA group (p < 0.05). Moreover, no statistically notable distinction was observed in terms of postoperative hospitalization duration and overall hospitalization duration among both groups (p > 0.05). According to the study, both the CIVIA group and the TIVA group had a total of 7 (13.72%) and 17 (32.07%) individuals, respectively, who met the criteria for neurocognitive delayed recovery (Odds Ratio: 0.336; 95% CI: 0.134–0.864; p = 0.026). According to the research findings, it is indicated that there is a possibility for an increased presence of IL-6 in the bloodstream within 60 min following the incision made on the skin. This occurrence subsequently leads to the prolonged restoration of neurocognitive capabilities. Conclusion The CIVIA technique outperforms the TIVA method in terms of overall assessment in the setting of laparoscopic surgery. It’s also important to remember that an increased blood IL-6 level during laparoscopy may operate as a separate risk factor for a delay in the restoration of neurocognitive function.